2020
DOI: 10.3892/or.2020.7844
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-134-3p inhibits ovarian cancer progression by targeting flap structure-specific endonuclease 1 in vitro

Abstract: Ovarian cancer (OC) is one of the most lethal gynecological malignancies in the world. The aim of the present study was to examine the role of microRNA (miR)-134-3p in OC. Reverse transcription-quantitative PCR was used to measure the expression levels of miR-134-3p. Cell Counting Kit-8, TUNEL, flow cytometric and colony formation assays were performed to examine the effects of miR-134-3p on OC cell proliferation. Moreover, wound healing and Transwell assays were performed to examine the effects on migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Many miRNAs have been determined to be involved in the development of ovarian cancer. MiR-134-3p inhibited the progression of ovarian cancer via targeting flap structure-specific endonuclease 1 in vitro (Zhao et al 2020 ). MiR-195 regulated tumor growth and MICU1 expression in ovarian.…”
Section: Discussionmentioning
confidence: 99%
“…Many miRNAs have been determined to be involved in the development of ovarian cancer. MiR-134-3p inhibited the progression of ovarian cancer via targeting flap structure-specific endonuclease 1 in vitro (Zhao et al 2020 ). MiR-195 regulated tumor growth and MICU1 expression in ovarian.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR-134-3p has been described by others to inhibit cancer progression. For example, in ovarian cancer it was demonstrated that miR-134-3p overexpression lowered ovarian cancer cell proliferation and caused cell cycle arrest as well as migration and invasion [36]. With respect to ovarian cancer, the effects were partially caused by down-regulated expression of FEN1 mediated by miR-134-3p [36].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in ovarian cancer it was demonstrated that miR-134-3p overexpression lowered ovarian cancer cell proliferation and caused cell cycle arrest as well as migration and invasion [36]. With respect to ovarian cancer, the effects were partially caused by down-regulated expression of FEN1 mediated by miR-134-3p [36]. Also, for small-cell lung cancer, a tumor-suppressive function of miR-134 was shown.…”
Section: Discussionmentioning
confidence: 99%
“…This has been observed in cervical cancer, breast cancer, and non-small cell lung cancer (NSCLC) [ 11 13 ]. A study revealed that miR-134-3p, a FEN1 inhibitor, considerably decreased cell proliferation, migration, and invasion and increased apoptosis in human ovarian cancer [ 14 ]. However, the function of miR-4324 and FEN1 in ovarian cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%